Textual Metafunction in The Choir Traditional Spiritual Song “Elijah Rock” By Moses Hogan - Rajagukguk, Rosdiana; Siahaan, Sahat Taruli (Journal of Language Development and Linguistics, 2024)
This research explores the textual metafunction of the choir song "Elijah Rock" by Moses Hogan through the lens of Systemic Functional Linguistics (SFL), employing Suzanne Eggins' model of analysis. By examining the song's lyrical structure, the study aims to uncover how thematic organization, cohesion, and information flow contribute to the overall meaning and emotional impact of the piece. The analysis identifies key thematic elements, such as the recurring motif of "Elijah," as topical theme; the use of other topical themes such as: “come on”, “tell”, “comin’ up”,  “Satan”; “He”; and “I”; the use of textual theme “if” and “Oh” highlights the extensive use of repetition and parallelism, which enhance textual coherence. Through a qualitative content analysis, the research demonstrates how linguistic features not only create a unified text but also resonate with the cultural and historical significance of African American spirituals. The findings reveal that the interplay between textual structure and musical expression plays a vital role in conveying the song's message and engaging audiences. This study contributes to the growing body of literature on the intersection of linguistics and music, offering valuable insights for future research in both fields.